Projeto preliminar de um disco centrífugo para distribuição de uréia - Silva, Elton Neves da (2011)
Recognizing the increasing complexity of today's farm machinery, and the trend of progression of this feature for new developments it is important to the implementation of models for the structured and systematic approach to information related to the development of new machines or techniques. Errors in defining the problem has caused frustration and wasted time in the development process of agricultural machinery. Thus, design is a set of procedures and specifications that, if implemented, result in something concrete or in a set of information. Distributors centrifugal technology revolutionized the application of solid products in agriculture by great field operational capacity and wide range of doses that can be applied. The study aims, design a centrifugal disk for distribution of urea using the fundamentals of the theory of flow machines. The machines on the market distribute various types of fertilizers and variable rates. What is happening is a great similarity in the principles of solution in the dispenser system / distributor. However, there may this equipment has some disadvantages such as difficulty in applying the material evenly on the working width used even as an apparent ease of adjustment. The methodology for the development of the study is based on exploratory research of existing literature, preliminary design of a disk centrifuge and computer simulation in order to test concepts. Designs were modeled six discs, three format and three plan of conical shape, with variations in the number and length of fins, through the systematization of knowledge among dispensing machines and machines to haul flow. Was obtained between the layouts of the simulation, the disc with tapered curved fins 7, the flat disc with curved vanes 6 alternate, tapered disk with 6 curved vanes and disc cone alternating with 6 curved vanes, able to alter the distribution profile increase the percentage of deposition on the soil and correct the application uniformity by overlapping.